Cerebral plasticity as the basis for upper limb recovery following brain damage. (April 2019) - Lotze, Martin; Ladda, Aija Marie; Stephan, Klaus Martin
Highlights: Neural basis for training and plasticity in healthy volunteers. Non-invasive methods to observe processes of neural plasticity. Postlesional plasticity and training in animals and in humans. Biomarkers for prediction of motor outcome and therapy planning. Abstract: Neural plasticity is the basis for an adaptation process of functional and structural characteristics of the nervous system in response to a changing environment. However, changes during training in healthy volunteers are only partially comparable to that observed in patients with circumscribed lesions. Pathologies can even be associated with maladaptive plasticity. We first introduce basic processes underlying brain plasticity with respect to the sensorimotor system and outline their limitations. A number of methods showing potential in the evaluation of these processes are compared before literature on postlesional plasticity is reviewed. Approaches in monitoring plasticity processes of the healthy sensorimotor system are partially applicable after brain damage and for the documentation of recovery processes. Some of these techniques can further be used for outcome prediction or therapy selection and optimization. Extreme examples from athletes or professional musicians illustrate the amount of plastic changes the human brain can achieve. Profound understanding of neural plasticity in health and disease will help to modify and individually optimize therapy strategies in neurorehabilitation.